Docetaxel-induced cognitive impairment in rats can be ameliorated by edaravone dexborneol: Evidence from the indicators of biological behavior and anisotropic fraction - Liu, Ping; Liu, Hai; Wei, Lijun; Shi, Xun; Wang, Wei; Yan, Shengxiang; Zhou, Wenya; Zhang, Jiangong; Han, Suxia (Frontiers in Neuroscience, 2023)
Objective This study aimed to investigate the effect of Edaravone Dexborneol (ED) on impaired learning and memory in docetaxel (DTX)-treated rats using cognitive behavior assessments and magnetic resonance diffusion tensor imaging (DTI). Materials and methods In total, 24 male Sprague–Dawley rats were divided into control, low-dose DTX (L-DTX) model, and high-dose DTX(H-DTX) model groups, with eight rats in each group, numbered 1–8. The rats were intraperitoneally injected with 1.5 mL of either normal saline (control group), or 3 mg/kg and 6 mg/kg DTX (L-DTX and H-DTX groups, respectively), once a week for 4 weeks. The learning and memory abilities of each group were tested using a water maze. At the end of the water maze test, rats 1–4 in each group were treated with ED (3 mg/kg, 1 mL), and rats 5–8 were injected with an equal volume of normal saline once a day for 2 weeks. The learning and memory abilities of each group were evaluated again using the water maze test, and the image differences in the hippocampus of each group were analyzed using DTI. Results (1) H-DTX group (32.33 ± 7.83) had the longest escape latency, followed by the L-DTX group (27.49 ± 7.32), and the Control group (24.52 ± 8.11) having the shortest, with the difference being statistically significant (p < 0.05). (2) Following ED treatment, compared to rats treated with normal saline, the escape latency of the L-DTX (12.00 ± 2.79 vs. 10.77 ± 3.97, p < 0.05), and the H-DTX (12.52 ± 3.69 vs. 9.11 ± 2.88, p < 0.05) rats were significantly shortened. The residence time in the target quadrant of H-DTX rats was significantly prolonged (40.49 ± 5.82 vs. 55.25 ± 6.78, p < 0.05). The CNS damage in the L-DTX rats was repaired to a certain extent during the interval between the two water maze tests (28.89 ± 7.92 vs. 12.00 ± 2.79, p < 0.05). (3) The fractional anisotropy (FA) value of DTI in the hippocampus of rats in the different groups showed variable trends. After treatment with ED, though the FA values of most areas in the hippocampus of rats in L-DTX and H-DTX groups were higher than before, they did not reach the normal level. Conclusion ED can ameliorate the cognitive dysfunctions caused by DTX in rats by improving the learning and memory impairment, which is reflected in the recovery of biological behavior and DTI indicators of the hippocampus.